2009
DOI: 10.1364/oe.17.006245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface manufacturing error of cubic phase mask in wavefront coding system

Abstract: The degenerated performance of extend depth of field (EDoF) in wavefront coding system which using cubic phase mask is simulated. A periodical rotationally symmetric surface error structure is presented and combined with comparison the similarity of point spread function (PSF). The peak to valley (PV) error of the cubic surface is needed smaller than 15% compare with the sag of the cubic surface for low period error existed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Correlation coefficient is previously utilized to calculate similarity of PSF for different defocus aberration in wavefront coding imaging system [22]. This paper uses it to measure the PSF consistency between the changed-temperature PSF and the room temperature PSF, which can be represented as follows,…”
Section: Calculation Of Psf Consistency After Temperature Variationmentioning
confidence: 99%
“…Correlation coefficient is previously utilized to calculate similarity of PSF for different defocus aberration in wavefront coding imaging system [22]. This paper uses it to measure the PSF consistency between the changed-temperature PSF and the room temperature PSF, which can be represented as follows,…”
Section: Calculation Of Psf Consistency After Temperature Variationmentioning
confidence: 99%
“…Figure (2) shows schematically the finished etalon on a standard image sensor. Our device utilized a commercially available imaging sensor provided by Aptina® (MT9V111), a standard FSI (front side illuminated) CMOS imager.…”
Section: /Hh2014/$25©2014trfmentioning
confidence: 99%
“…In order to simulate sampling effect from finite pixel size in image sensor, two metrics are presented, one is similarity of PSF and the other is MSE of restored image which MMSE filter is applied for deconvolution. The definition of PSF similarity was already used in our prior studies [14][15][16]18], which can be written as Eq. (1):…”
Section: Psf Similarity and Image Metric For Restored Imagementioning
confidence: 99%
“…For IR imaging system, Muyo has shown that surface error of generalized cubic should be around 1/10 wavelength [13]. And also our prior studies have shown that surface error of phase coding element is critical and the effects of mid-frequency of surface error were discussed [14][15][16].…”
Section: Introductionmentioning
confidence: 97%